Interactive online physics labs increase high school students' interest - Patrick Gryczka; Edward Klementowicz; Chappel Sharrock; Jin Montclare (OmniaScience, 2016)
Here we describe the incorporation of a web-based application focusing on circuits for the physics high school classroom as part of an outreach program. The program involves college mentors creating and implementing science lessons in collaboration with the classroom teacher. Focusing on the challenge of understanding circuit design, a technology rich module is employed to improve learning and motivation of the students. The students' conceptual understanding as well as interest in circuits was increased, the college mentors earned valuable teaching and mentoring experience and the teacher enjoyed more one-on-one time as well as assistance with students.